Iranian Health Research Networks and Vision of Iran by 2025: A Case of Virtual Health Network in EMRI. - Aa Keshtkar; Sh Djalalinia; P Khashayar; N Peykari; Z Mohammdi; B Larijani (Tehran University of Medical Sciences, 2013)
The present paper aims to explore the role of Health Research Networks (HRN) in facilitating and expedite achieving the prospects for goals of health research based on the visions of Iran by 2025.Aiming to the main function of HSR to achieve the targeted conducting of health sciences research; more cooperation and coordination between health science researchers; avoid parallel investigations; and optimum utilization and appropriate distribution of resources, in 2000 the deputy of Research and Technology of Ministry of Health and Medical Education defined and developed a comprehensive HRN.There are currently 27 research networks operating under the supervision of the Deputy of Research and Technology at MOHME. All of the HRN policies are following based on their strategic planning's which are extracted from national visions of Iran by 2025.Promoting the current position needs a reliable and feasible new strategies. The present article introduces the lessons learned of our experience in virtual web-based health research networking in Endocrinology and Metabolism Research Institute (EMRI).